Optimising healthcare ICT support for the care and management of elderly adults with mental illness in residential aged care facilities. (10th June 2016) - Bosua, Rachelle; Lederman, Reeva; Van Zyl, Karen
Abstract: The global increase of adult mental illness (Dementia and Alzheimer) in the 65 years and older age group, pose unique treatment challenges to residential aged care facility staff. Current residential aged care mental illness treatment plans for elderly adults are not customised according to individual personal needs. Such customization requires inputs from multiple stakeholders i.e. mentally ill adults, carers, medical professionals and clinicians, community mental healthcare service providers, family/relatives and friends. This research aims to develop an integrated ICT framework that supports customised treatment plans for adults with mental illness in residential aged care facilities. This research-in-progress outlines initial stages of a novel methodology to better support and enable individual care and treatment of adults with mental illness in residential aged care facilities. Application of this methodology will 1) identify key information needs for individualised mental illness treatment plans, 2) integrate and consolidate multiple information sources, 3) enhance aged care facility carers' experience and understanding of the impact of mental illness on human behaviour, and 4) implement innovative ICT solutions that support individualised care and treatment plans.